2020
DOI: 10.3389/fimmu.2020.00649
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of Acute Chorioamnionitis

Abstract: Acute chorioamnionitis is characterized by neutrophilic infiltration and inflammation at the maternal fetal interface. It is a relatively common complication of pregnancy and can have devastating consequences including preterm labor, maternal infections, fetal infection/inflammation, fetal lung, brain, and gastrointestinal tract injury. In this review, we will discuss current understanding of the pathogenesis, immunobiology, and mechanisms of this condition. Most commonly, acute chorioamnionitis is a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 291 publications
(318 reference statements)
1
56
0
6
Order By: Relevance
“…However, some pathogens can escape antimicrobial strategies at the cervix and ascend to the uterus, where they can bypass the fetal membranes and lead to the inflammation of the membranes- also known as chorioamnionitis- and infection of the amniotic fluid ( 7 , 8 ). Pathologic and immune features of chorioamnionitis and intra-amniotic infection are generally associated with bacterial invasion and inflammation [refer to ( 8 , 9 ) for a comprehensive review on these mechanisms]. Here, we focus on infections and innate immune mechanisms at the uterine-placental interface—cases (i) and (ii) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some pathogens can escape antimicrobial strategies at the cervix and ascend to the uterus, where they can bypass the fetal membranes and lead to the inflammation of the membranes- also known as chorioamnionitis- and infection of the amniotic fluid ( 7 , 8 ). Pathologic and immune features of chorioamnionitis and intra-amniotic infection are generally associated with bacterial invasion and inflammation [refer to ( 8 , 9 ) for a comprehensive review on these mechanisms]. Here, we focus on infections and innate immune mechanisms at the uterine-placental interface—cases (i) and (ii) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is well-known that intra-amniotic micro-organisms incite an IAIR resulting in an increase of chemokine level (e.g., CXCL6, IL-8) and chemotactic gradient [3,7,14,15]. Ultimately, this phenomenon causes amniotrophic outside-in neutrophil migration within EPM [7,14]. The extent Our previous studies demonstrated IAIR increased according to the progression of inflammation in the detailed subdivisions of each placental compartment [25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados de las pruebas de laboratorio pueden ayudar a descartar el diagnóstico de corioamnionitis, especialmente cuando los signos y síntomas clínicos son equívocos. La leucocitosis materna (definida de manera diversa como WBC> 12,000 / mm3 o> 15,000/mm3) o la presencia de un desplazamiento a la izquierda o una bandemia (> 9%) a menudo respaldan el diagnóstico de corioamnionitis (12). Se informa leucocitosis en aproximadamente el 70-90% de los casos de corioamnionitis clínica.…”
Section: Discussionunclassified